The passive and active contractile properties of the neurogenic, underactive bladder. (19th June 2012) - Young, John S.; Johnston, Louise; Soubrane, Camille; McCloskey, Karen D.; McMurray, Gordon; Eccles, Rachel; Fry, Christopher H.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Detrusor underactivity is highly prevalent, particularly in the elderly. It is assumed to result from detrusor failure, although detrusor contractility is often derived from urodynamics studies. Given that detrusor pressure and force are not proportional and urodynamics cannot identify the basis of the pathology, we produced a neurogenic animal model with a highly‐compliant bladder and studied detrusor muscle properties, aiming to increase our understanding of the underlying pathology. Highly compliant bladders were characterized by reduced passive wall stiffness and stretched detrusor muscle strips exhibited an enhanced rate of relaxation. These detrusor strips displayed spontaneous contractions that were of greater amplitude (expressed as a ratio of bladder wall stiffness) than those of strips from sham‐operated animals; spontaneous contractions increased in amplitude when stimulated by an agonist. These data imply that compliance is not the result of a reduction of detrusor contractility; we hypothesize that altered matrix properties reduce the magnitude with which force can be generated to void the bladder. Objective To characterize passive and active changes in detrusor activity in a highly compliant bladder. Materials and Methods Bladders from adult female Sprague–Dawley rats were used 5 weeks after lower thoracic (T8) spinal cord transection or a sham‐operation. Passive wall properties were assessed by pressure–volume relationships from whole bladders and the tensile response of bladder strips after a rapid (<0.5 s) stretch. Active properties were assessed from the frequency and amplitude of spontaneous contractions of bladder strips, and their response to the inotropic TRPV4 agonist GSK1016790A. Results Passive bladder wall stiffness of SCT bladders was significantly reduced compared to that of the sham‐operated control group (N = 6 and 8, respectively) and SCT bladder strips relaxed more quickly than those from sham‐operated rats. The frequency of spontaneous contractions was reduced in SCT rats, and their amplitude, expressed as a ratio of bladder wall stiffness, was greater than in sham‐operated rats. GSK1016790A (0.1 μM) significantly increased amplitude in strips from both sham‐operated and SCT groups. Conclusions There is no evidence of contractile failure in a highly‐compliant bladder. The observations of reduced passive bladder wall stiffness and an enhanced rate of stress relaxation lead to the conclusion that increased compliance is marked by altered matrix properties that dissipate muscle force, thereby generating low pressures. Contractile agonists may be effective for improving bladder function in detrusor underactivity.